Shipping the good agricultural products out: the differentiated impact of per-unit duties on developing countries. (13th September 2020) - Emlinger, Charlotte; Guimbard, Houssein
Abstract: We investigate the impact of per-unit duties (i.e. tariffs expressed in US dollars per unit of imported product) on world agricultural trade patterns. Using detailed data on trade and tariffs, we show first that they induce higher export unit values, confirming that the Alchian–Allen conjecture can be extended to per-unit duties. Second, we show that this effect is higher for developed countries, which can be explained by their specialization on high-priced products. Third, we find that the restrictive effect of per-unit duties on trade is higher for developing countries.